A Case of Carcinoid Heart Disease with Desaturation and No Liver Metastases. Issue 10 (5th August 2014) - Requilé, Annelies; Van De Bruaene, Alexander; Reenaers, Veerle; Dendale, Paul
Mini‐Abstract In 95% of cases of carcinoid heart disease, the primary tumor is located in the gastrointestinal tract and hepatic inactivation of serotonin prevent symptoms from occurring until liver metastases are present. Ovarian carcinoid tumors are an unusual cause of carcinoid heart disease in the absence of liver metastases. Rarely, carcinoid heart disease is associated with desaturation due to right‐to‐left shunting through a patent foramen ovale. We present the case of a 64‐year‐old female with carcinoid heart disease without liver metastases and hypoxemia due to right‐to‐left shunting.